Route to pyrrolo[1, 2-a]quinoxalines via a furan ring opening-pyrrole ring closure sequence. Issue 9 (27th February 2020) - Zelina, Elena Y.; Nevolina, Tatyana A.; Sorotskaja, Ludmila N.; Skvortsov, Dmitry A.; Trushkov, Igor V.; Uchuskin, Maxim G.
Graphical abstract: Highlights: Route for the synthesis of functionalized pyrrolo[1, 2- a ]quinoxalines was developed. The hydrolysis of N -protected furfurylamines produced 1, 4-diketones in high yields. The reductive Paal-Knorr reaction afforded the target pyrrolo[1, 2- a ]quinoxalines. The cytotoxicity of obtained pyrrolo[1, 2- a ]quinoxalines was investigated. Abstract: A method was developed for the synthesis of pyrrolo[1, 2- a ]quinoxalines based on an acid-promoted furan ring opening of readily accessible N -(furan-2-ylmethyl)-2-nitroanilines or their heterocyclic analogues followed by a key reductive Paal-Knorr cyclization of the corresponding nitro-1, 4-diketones.